Effect of a community heart failure clinic on uptake of β blockers by patients with obstructive airways disease and heart failure. Issue 3 (10th June 2005) - Shelton, R J; Rigby, A S; Cleland, J G F; Clark, A L
Abstract : Objective: To determine the pattern of β blocker prescribing over one year in a heart failure clinic with a structured approach towards initiation and dose titration and to give a real life perspective on β blocker use, compliance, and target dose achievement. Methods: Data were retrospectively analysed on 513 consecutive patients regularly attending a community heart failure clinic over a year. Systolic dysfunction was determined from two dimensional echocardiography (left ventricular ejection fraction ⩽ 40%) and lung function was assessed by spirometry. All patients were considered for β blocker initiation and dose up titration. Results: Within one year 157 patients died. 143 patients started β blockers resulting in 315 (88%) patients taking β blockers at one year; 38% were taking the target dose. 124 had evidence of airways obstruction at baseline, 100 (81%) of whom were taking β blockers at one year. Forced expiratory volume in one second (1.1 v 1.5 l, p < 0.01) and forced vital capacity (2.3 v 2.5 l/min, p  =  0.2) were not reduced in patients with airways obstruction who received β blockers. Daily doses of β blockers at one year did not differ statistically between patients with obstructive and patients with non-obstructive spirometry results. 12 patients discontinued β blockers and 14 required dose reduction due to side effects. Conclusion: The majority of patients with heart failure and obstructive airways disease can safely tolerate low dose initiation and gradual up titration of β blockers.